Does The Core Tax Administration System Simplify Comppliance For Corporate Taxpayers? - Yunia Reza Herawati; Moh Faisol (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2026)
Taxpayer convenience refers to each taxpayer’s perception of whether an existing system is easy to use or not. To improve taxpayer convenience, the Coretax Administration System (CTAS) has been implemented; however, there are still complaints from taxpayers regarding this system. This study aims to examine the effect of CTAS on the convenience of corporate taxpayers. This research was conducted on corporate taxpayers in Sumenep Regency who registered at the KPP Pratama Pamekasan in 2024 in using CTAS, considering aspects of convenience, effectiveness, and efficiency. The research method used is quantitative with purposive sampling technique, resulting in 98 corporate taxpayers as research respondents. The hypothesis testing technique in this study is simple linear regression and T-test. The results of the study using the T-test show that the use of CTAS has a positive and significant effect on the convenience of corporate taxpayers in fulfilling their tax obligations. This is due to the integrated information technology through CTAS, which facilitates corporate taxpayers. The findings of this study can provide input for the Direktorat Jenderal Pajak (DJP) to evaluate the use of CTAS in improving more responsive tax services that meet taxpayer needs, thereby encouraging them to maximize the use of the system.